Global Classroom brings UMP and Kansai University students together - Nor Salwana, Mohammad Idris (2021)
KUANTAN, 30 June 2021 - The experience of participating in a global classroom gave pleasant memories for the students from Universiti Malaysia Pahang (UMP) and Kansai University (KU), Japan, when they met online at Kansai University - Digital Transformation (KU-DX) involving several international universities including the United States of America, the Philippines, Taiwan and Korea along with media representatives from Japan.